Efficient direct lignin fuel cells enabled by hierarchical nickel–iron phosphide nanosheets as an anode catalyst. Issue 21 (28th September 2022) - Liu, Fei; Lusi, A.; Radhakrishnan, Harish; Liu, Hengzhou; Li, Wenzhen; Qin, Hantang; Jiang, Shan; Bai, Xianglan; Shan, Hu
Abstract : Hierarchical nickel–iron phosphide nanosheets were reported as a novel anode catalyst for direct lignin fuel cells at low temperature. When NiFeP with a Ni/Fe ratio of 1 was used, the fuel cell produced a maximum power density of 24 mW cm −2 . Abstract : Lignin fuel cells are an emerging technology to sustainably produce electricity from renewable natural resources. A high-performance anode catalyst is highly desirable to enhance the power density of lignin fuel cells for practical applications. Here we demonstrated hierarchical nickel–iron phosphide (NiFeP) nanosheets as a novel anode catalyst for direct lignin fuel cells (DLFCs) at low temperature. NiFeP was grown on nickel foam with its stoichiometry readily controlled in the synthesis. When NiFeP with a Ni/Fe ratio of 1 was used, the fuel cell produced a maximum power density of 24 mW cm −2, over 200 times higher than that of microbial fuel cells or alkaline fuel cells. This performance is comparable to liquid flow fuel cells using liquid catalysts. The P incorporation in NiFeP was found to be essential, whereas P leaching resulted in a significant loss of activity, and re-phosphorization of the used catalyst can recover up to ∼80% of the freshly prepared catalyst. In addition, hierarchical nanostructures consisting of 2D nanosheets were also beneficial. The power density of lignin fuel cells could be further improved when the cell was fed with purified lignin with less inorganic ash. Our work provided a new platform of anode catalysts for power generation from biomass.